Reproductive diapause in Hippodamia convergens (Coleoptera: Coccinellidae) and its life history consequences - Michaud, J. P.; Qureshi, Jawwad A. (My University, 2012)
Adult Hippodamia convergens (Guerin) in reproductive diapause were collected from a spring cohort in western Kansas and held in pairs for the duration of their lives to assess female reproductive schedules under conditions of limited food availability. Environmental conditions were set to mimic natural seasonal day lengths and diurnal temperature cycles for the region. To approximate conditions of limited food availability typical of summer conditions in western Kansas, beetles were provided continuous access to sunflower petioles and periodic access to protein sources, both animal (Ephestia kuehniella Zeller eggs) and vegetable (bee pollen). A total of 113 out of 171 females (66.1%) became reproductive over the next five months within a mean of 55.0 ± 3.0 day. These females lived an average of 134.5 ± 4.6 day and produced a mean of 106.9 ± 11.6 eggs in a mean of 6.6 ± 0.6 day of oviposition. Thus, reproductive diapause gradually decayed over time even when females did not encounter a high quality food supply. Egg production peaked every fourth day following provision of animal protein. A subset of 20 females, randomly selected from among those still non-reproductive on August 14 and switched to an aphid diet (ad libitum provision of Schizaphis graminum (Rondani)) produced a mean of 654.6 ± 109.7 eggs each, almost 10 times as many as females on the maintenance diet with similar reproductive schedules. However, the longevity of greenbug-fed females was reduced by more than 30% compared to the latter group, suggesting a tradeoff between reproductive effort and survival. The costs of reproductive diapause were evident as an increased risk of mortality prior to oviposition and declining fecundity and fertility with age. Our results suggest a variable number of overlapping generations can occur annually in western Kansas, potentially as many as five.
Citation: Michaud, J.P., & Qureshi, J.A. (2006). Reproductive diapause in Hippodamia convergens (Coleoptera: Coccinellidae) and its life history consequences. Retrieved from http://krex.ksu.edu
Keywords: Diapause; Diet; Fecundity-longevity trade-off; Hippodamia convergens; Reproduction; Schizaphis graminum